The Effect of Training And Utility on The Implementation of Electronic Medical Record With Organizational Culture as A Moderator - Yunita, Fina (Journal of Hospital Management, 2025)
This research is based on the problem  of satisfaction with the implementation  of electronic medical records that have not maximally satisfied nurses as users. The purpose of this study is to empirically reveal the influence of training and utility on the implementation of electronic medical records with organizational culture as a moderator. This study is included in a quantitative study with  a cross sectional study design, the population is outpatient installation nurses with civil servant status, the sampling technique uses a saturated sample so that the number of samples is set at 77 respondents. The analysis method used was the three box method and PLS-SEM analysis. The results of the analysis concluded that training, utilities and organizational culture had a positive and significant effect on the implementation of electronic medical records, organizational culture did not moderate the influence of training and utilities on the implementation of electronic medical records.